EXISTENCE OF RATOH BANTAI DANCE IN THE STUDIO OF BUANA BANDA ACEH - Fifie Febryanti Sukman; Sabri Gusmail (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
Ratoh Bantai dance is one of traditional dances from South Aceh that has its unique characteristics. According to its name, Ratoh Bantai uses property that is different from ordinary dances in Aceh province namely pillow. In the past, this dance became the popular dance in the society but the appearance of various dances that are more upbeat and energetic make Ratoh Bantai dance starting to become unpopular in the society. This research took the subject “effort of maintaining the existence of Ratoh Bantai dance. The purposes of this research are to know and describe the effort of maintaining the existence of Ratoh Bantai dance. Research method used is descriptive qualitative method. Data were obtained through observation, interview, and library research. Research result obtained is Buana studio as one of studios that maintain the traditional dance of Ratoh Bantai conducts teaching effort to its protégés in the studio every month so the protégés of Buana studio still know the repertoire of dances in Aceh, especially Ratoh Bantai dance that’s almost forgotten by today young generation. Besides that, this research also described the choreography aspect of Ratoh Bantai dance in Buana studio.